2018
DOI: 10.1007/s00586-018-5820-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of bony fusion after anterior cervical discectomy: a systematic literature review

Abstract: Purpose Anterior cervical discectomy and fusion (ACDF) has proven effective in treating radicular arm pain. Post-operatively, cervical spine stability is temporarily challenged, but data on bony fusion and speed of fusion are ambiguous; optimum evaluation method and criteria are debated. Aim To study bony fusion accomplishment and to obtain an overview of methods to evaluate fusion. Methods A literature search was performed in PubMed and Embase. Included studies had to report original data concerning 1-or 2-le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(25 citation statements)
references
References 119 publications
1
23
0
1
Order By: Relevance
“…In previous studies, the fusion rate of two-level ACDF varied; a systematic review [ 10 ] reported a mean fusion rate of 90.1%, which ranged from 30 to 100%. Smoking, osteoporosis, diabetes, preoperative range of motion (ROM), and preoperative T1 slope are the factors that influence the fusion rate or fusion speed [ 11 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies, the fusion rate of two-level ACDF varied; a systematic review [ 10 ] reported a mean fusion rate of 90.1%, which ranged from 30 to 100%. Smoking, osteoporosis, diabetes, preoperative range of motion (ROM), and preoperative T1 slope are the factors that influence the fusion rate or fusion speed [ 11 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Midterm follow-up of the clinical and radiological results achieved by tantalum intervertebral fusion cages for single-level ACDF have shown that the cages remain in good condition for up to 11 years postoperatively, and similar results with the use of autologous bone grafts and plating were also reported [7]. The use of plates and fusion cages with screws can promote fusion, but no clinically significant differences have been shown [8]. Kettler et al [9] reported that the design of the implants used determines the relationship between the activity and the subsidence rate.…”
Section: Introductionmentioning
confidence: 99%
“…Even in the absence of ideal criteria at present, the combination of X-rays with flexion-extension X-rays and CT scans was frequently used for determining clinical fusion quality after a cervical spine surgery [19,20]. For animal studies, several methods with different advantages and limitations are available for evaluation of spinal fusion including X-rays, CT scans, magnetic resonance imaging (MRI), micro-CT scans, biomechanical tests, histologic analysis, bone mineral density tests and other uncommon methods.…”
Section: Discussionmentioning
confidence: 99%